ANALISIS EFEKTVITAS PROGRAM REVITALISASI PASAR TRADISIONAL DI PASAR BULU KOTA SEMARANG - Iis Nurlaela; Dyah Hariani (Journal of Public Policy and Management Review, 2017)
The existence of traditional market be on the skids here with rapid development of modern market. Presence of modern market that managed professionally claimed have been discrediting the presence of traditional market. Revitalization of traditional market is the effort to keep the existence of traditional market and increasing the competitiveness traditional market against modern market. This research is aim to analize the effectiveness of traditional market revitalization program in Pasar Bulu Semarang City and identifying the barrier factors of effectiveness revitalization program. The research result shows that traditional market’s revitalization program in Pasar Bulu Semarang City is not effective because not any change mindset of traders from traditional market to modern traditional market, decline acceptance of retribution in Pasar Bulu, funding revitalization is not allocated efficiently to build complete facilities in accordance with provisions, community dissatisfaction with information service in Pasar Bulu, a descline in the income of traders, not many people community invilvement in express their opinions, traders attitude and visitors can’t keep the cleanliness and discipliness of the market, a lot of facilities defect numbers that not repaired soon, and market maintener haven’t been able to enforce rules firmly shows with a lot numbers of problem that seems to be left and not followed soon.